Perspectivas de atores escolares: quais possibilidades de atuação do psicólogo na educação básica - Goncalves, Eliane de Siqueira (2022)
The promulgation of the Law 13,935, from December 11, 2019, which regulates psychology and social work in public education networks, is the begining of a scenario marked by concerns regarding the performance, role and specificities of the psychologist at school. Thus, this study aimed to describe the conceptions of students in the final years of elementary school, of their respective mothers and school professionals about the possibilities of performance of the psychologist in basic education. The theoretical referential used in this work was related to subjects that encompass the area of school psychology, with a broad and social view to the factors that interfere in learning, considering all the actors involved in the process, such as society, family, school professionals and students. References from human development theories were also used, more specifically focused on the period of adolescence. This was a qualitative and descriptive research and 36 participants were interviewed: six managers (principals, vice principal and pedagogue na others); a general services assistant; eleven teachers from the final years of the elementary school; nine students from the seventh, eighth and ninth years of elementary school, and mothers of the the nine students interviewed. The data analysis was based on Delval's proposal. After collecting the data the interviews were transcribed and six categories were created: family relationships and influence on the student's school career; the work of professionals in the school context; adolescence as a negative interference in students' behavior; student's relationship with the school context; affection as a promoter of development and learning, unfamiliarity with the performance of the school psychologist - which was subdivided into three subcategories: possibility of insertion of the psychologist in basic education; the public with whom the psychologists are going to work with at school and, the contribution of the psychologists according to the perception of the school actors. The results showed the participant’s perception about the difficulties of school actors in the school context, separation from families and blaming this public for students' school problems, exhaustion of school professionals caused by their work, stigmatized view of adolescence as a troubled period, school disinterest by the students, the importance of building relationships of affection in the school context. In addition, regarding the performance of the school psychologist, the interviewees are unaware of it, although mosto f the wanted the professional's insertion in school environments, as far as They understand that the predominant public of action are the students. The data allow us to observe that the participating school actors understand the contribution about the role of school psychology that is not consistent with the theoretical and interventionist references that exist scientifically today. In this sense, it is necessary to disseminate knowledge and questions about different perceptions and expectations discussed in this research that do not address the difficulties in the school field. Furthermore, it is necessary that school actors, secretariats and federal and municipal managers, politicians, as well as the psychologists themselves and the society as a whole, understand the role of school psychology and realize that, in the school context, there are several broad interferences of the social, economic and historical contexts that affect the schooling process. This dissemination of knowledge can also be a way for all the publics mentioned above to demand the implementation of the federal law, in an ethical and scientific way, in the insertion of the school psychologist in the field of action. In addition, it is also possible to expand the discussion spaces so that it is not restricted to academics and researchers.